2023
DOI: 10.1177/17539447231168471
|View full text |Cite
|
Sign up to set email alerts
|

Identification of biomarkers, pathways, and potential therapeutic targets for heart failure using next-generation sequencing data and bioinformatics analysis

Abstract: Background: Heart failure (HF) is the most common cardiovascular diseases and the leading cause of cardiovascular diseases related deaths. Increasing molecular targets have been discovered for HF prognosis and therapy. However, there is still an urgent need to identify novel biomarkers. Therefore, we evaluated biomarkers that might aid the diagnosis and treatment of HF. Methods: We searched next-generation sequencing (NGS) dataset (GSE161472) and identified differentially expressed genes (DEGs) by comparing 47… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 263 publications
(255 reference statements)
0
2
0
Order By: Relevance
“…Despite the preliminary nature of the data, some changes in the proteome are intriguing and pertinent for potential future therapeutic approaches for renal diseases. OTOA protein, which was associated to blood pressure in this study, has recently been identified as a potential target for a kidney disease in which scar tissue forms on the glomeruli (Ganekal et al, 2023), a kidney structure that is damaged in kidney failure.…”
Section: Discussionmentioning
confidence: 75%
“…Despite the preliminary nature of the data, some changes in the proteome are intriguing and pertinent for potential future therapeutic approaches for renal diseases. OTOA protein, which was associated to blood pressure in this study, has recently been identified as a potential target for a kidney disease in which scar tissue forms on the glomeruli (Ganekal et al, 2023), a kidney structure that is damaged in kidney failure.…”
Section: Discussionmentioning
confidence: 75%
“…Among the chosen biomarkers, we picked potassium for screening analysis, considering the inherent importance of electrolytes in diagnostics and the clinical role of potassium as a health indicator [12,13,[51][52][53][54][55][56]. Furthermore, several studies have been performed using nextgeneration platforms, showing the differential expression of biomarkers, including omic biomarkers or protein and gene expression of these biomarkers and others related to potassium, in the context of mortality or cardiac complications [57][58][59][60][61][62][63][64][65]. While biomarkers such as troponin and albumin have established correlations with cardiac function, predicting mortality and AA, we opted to focus on potassium as a singular biomarker to test its predictability for different outcomes.…”
Section: Discussionmentioning
confidence: 99%